UPAYA GURU DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA DAN MENULIS SISWA KELAS I SDN 177 PEKANBARU - Sri Ramahdani; Dea Mustika (STKIP Subang, 2023)
The problems that often occur in grade I are related to reading and writing. The difficulties experienced by students when reading and writing activities are that students find it difficult to distinguish several letters such as letters d from letters b and p, and reading is still not fluent. The purpose of this research is to describe the strategies and methods used by the teacher to improve the reading and writing skills of grade I students. This research method is qualitative with a case study type. Data collection techniques are using interviews, observation and documentation. The data source involved 2 teachers and 4 students. Testing the validity of the data using triangulation. Data analysis techniques namely data collection, data reduction, data presentation and drawing conclusions. The results of the study show that the teacher has made efforts to develop students' reading and writing skills even though they have not shown maximum results such as the lack of use of interesting learning media in the learning process. The inhibiting factor for the teacher's efforts to develop reading and writing skills is the ability of students who are not the same, then the class atmosphere is not conducive and there is a lack of guidance from parents to accompany their children when studying at home, causing a lack of interest in student learning. The conclusion from the research results is that the efforts made by the teacher in developing reading and writing skills are using the spelling method, using interesting teaching materials and learning media, the teacher also gives additional hours to students who are not fluent in reading and writing, and there is collaboration between parents and teachers in developing students' reading and writing abilities